2022
DOI: 10.3390/sym14091866
|View full text |Cite
|
Sign up to set email alerts
|

Study of a Viscous ΛWDM Model: Near-Equilibrium Condition, Entropy Production, and Cosmological Constraints

Abstract: Extensions to a ΛDM model have been explored in order to face current tensions that occur within its framework, which encompasses broadening the nature of the dark matter (DM) component to include warmness and a non-perfect fluid description. In this paper, we investigated the late-time cosmological evolution of an exact solution recently found in the literature, which describes a viscous warm ΛDM model (ΛWDM) with a DM component that obeys a polytropic equation of state (EoS), which experiences dissipative ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…In explaining the recent accelerated expansion of the Universe using dissipative effects in the matter sector, in the context of Einstein's gravity, it was shown that the presence of cosmological constant is essential to satisfy NEC during the evolution of the viscous fluid, that too for some particular choice of bulk viscous coefficient [27][28][29]. However, in such models where both dark energy and viscous matter are considered, the late accelerated expansion is driven mainly by the dark energy component, while the contribution by viscous matter remains significantly small.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In explaining the recent accelerated expansion of the Universe using dissipative effects in the matter sector, in the context of Einstein's gravity, it was shown that the presence of cosmological constant is essential to satisfy NEC during the evolution of the viscous fluid, that too for some particular choice of bulk viscous coefficient [27][28][29]. However, in such models where both dark energy and viscous matter are considered, the late accelerated expansion is driven mainly by the dark energy component, while the contribution by viscous matter remains significantly small.…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies on late acceleration by Cruz et al [27][28][29], based on Eckart's theory, authors inferred that the NEC can be satisfied for a particular viscous model (ζ ∝ ρ) in the context of Einstein's gravity, with warm DM (WDM) in the presence of a cosmological constant. This implies that the presence of a cosmological constant is deemed inevitable for the validity of the NEC in the context of Einstein's gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the profligacy of viscous fluids which includes the shear and bulk viscosity [32,[36][37][38][39]. In references [40][41][42][43][44][45][46][47][48][49][50], the impact of bulk viscous fluids in the late-time accelerating cosmos have been examined. However, in an expanding universe, a feasible process for viscous fluid formation is more difficult to find.…”
Section: Introductionmentioning
confidence: 99%